Faktor Protektif terhadap Cyberbullying: Sebuah Telaah Literatur Sistematik pada Konteks Indonesia - Prawitasari, Galuh; Mulawarman, Mulawarman; Mulyani, Petra Kristi (JURNAL KONSELING GUSJIGANG, 2024)
This study aims to identify the protective factors against cyberbullying in Indonesian context. The method used in this study is Systematic Literature Review (SLR) by searching for relevant articles through the Science Direct and Google Scholar databases. After implementing the Preferred Reporting Items for Systematic Reviews and Meta-Analytics (PRISMA), six articles were obtained according to inclusion and exclusion criteria. The results show that protective factors against cyberbullying can be internal or external. Positive self-concept, high empathy, and literacy about cyberbullying are identified as internal factors, whereas social support from peers and supportive school climate are identified as external factors. Among those various protective factors, social support from peers is found to be the main determinant of cyberbullying.